Mild and Short-Term Caloric Restriction Prevents Obesity-Induced Cardiomyopathy in Young Zucker Rats without Changing in Metabolites and Fatty Acids Cardiac Profile - Ruiz-Hurtado, Gema; García-Prieto, Concha F.; Pulido-Olmo, Helena; Velasco-Martín, Juan P.; Villa-Valverde, Palmira; Fernández-Valle, María E.; Boscá, Lisardo; Fernández-Velasco, María; Regadera, Javier; Somoza, Beatriz; Fernández-Alfonso, María S. (Frontiers in Physiology, 2017)
Caloric restriction (CR) ameliorates cardiac dysfunction associated with obesity. However, most of the studies have been performed under severe CR (30–65% caloric intake decrease) for several months or even years in aged animals. Here, we investigated whether mild (20% food intake reduction) and short-term (2-weeks) CR prevented the obese cardiomyopathy phenotype and improved the metabolic profile of young (14 weeks of age) genetically obese Zucker fa/fa rats. Heart weight (HW) and HW/tibia length ratio was significantly lower in fa/fa rats after 2 weeks of CR than in counterparts fed ad libitum. Invasive pressure measurements showed that systolic blood pressure, maximal rate of positive left ventricle (LV) pressure, LV systolic pressure and LV end-diastolic pressure were all significantly higher in obese fa/fa rats than in lean counterparts, which were prevented by CR. Magnetic resonance imaging revealed that the increase in LV end-systolic volume, stroke volume and LV wall thickness observed in fa/fa rats was significantly lower in animals on CR diet. Histological analysis also revealed that CR blocked the significant increase in cardiomyocyte diameter in obese fa/fa rats. High resolution magic angle spinning magnetic resonance spectroscopy analysis of the LV revealed a global decrease in metabolites such as taurine, creatine and phosphocreatine, glutamate, glutamine and glutathione, in obese fa/fa rats, whereas lactate concentration was increased. By contrast, fatty acid concentrations in LV tissue were significantly elevated in obese fa/fa rats. CR failed to restore the LV metabolomic profile of obese fa/fa rats. In conclusion, mild and short-term CR prevented an obesity-induced cardiomyopathy phenotype in young obese fa/fa rats independently of the cardiac metabolic profile.